2000
DOI: 10.1159/000017503
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Clinical Results of the FLQA-d, a Quality of Life Questionnaire for Patients with Chronic Skin Disease

Abstract: Background: Quality of Life (QoL) has become an important outcome parameter in dermatology. Although various dermatology- specific questionnaires have been developed in the last years, many methodological questions on how to evaluate QoL in skin diseases are still unanswered. We previously published the concept of a modular QoL instrument called Freiburg Life Quality Assessment (FLQA) with variants for the use in chronic venous insufficiency, leg ulcer and allergies. Objective: To develop, validate and test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 22 publications
0
40
0
6
Order By: Relevance
“…The questionnaire package included sociodemographic items, the German version of the Skindex-29 and 2 validated German skin disease-specific questionnaires: the Freiburger Life Quality Assessment for Dermatoses (FLQA-d) [21]and the Marburger Skin Questionnaire (MHF) [22]. In addition, sample II completed the internationally established Dermatology Life Quality Index (DLQI) [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire package included sociodemographic items, the German version of the Skindex-29 and 2 validated German skin disease-specific questionnaires: the Freiburger Life Quality Assessment for Dermatoses (FLQA-d) [21]and the Marburger Skin Questionnaire (MHF) [22]. In addition, sample II completed the internationally established Dermatology Life Quality Index (DLQI) [23].…”
Section: Methodsmentioning
confidence: 99%
“…In dermatology, studies have shown that HRQOL can be severely reduced in patients with a great variety of different skin diseases such as atopic dermatitis and psoriasis [3], acne vulgaris [4, 5], urticaria [6], skin tumours [7], port wine stains [8], onychomycosis [9]or chronic venous insufficiency and leg ulcers [10, 11, 12, 13]. Domains of everyday life that may be affected by skin diseases include aspects of physical and emotional well-being, the patients’ social life as well as their level of functioning at work or school.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a skin disease which has substantial socioeconomic bearing for several reasons: (1) it is a highly prevalent disease, affecting about 2–3% of adults in Western populations [1,2,3,4,5,6]; (2) it is a chronic disease which is associated with permanent or frequently recurring, highly visible and symptomatic skin lesions [7, 8]; (3) it leads to significant burden of disease and a reduction in quality of life (QoL) in patients from all countries [9,10,11,12]; (4) many patients with psoriasis are of working age, this results in work day loss, and therefore increased indirect costs (productivity losses). …”
Section: Introductionmentioning
confidence: 99%
“…The same is true for Bavaria where 18 % of patients had PASI > 20 and 41.8 % had DLQI > 10. These figures suggest a severely limited quality of life [23], as found in international studies in patients with severe forms of disease [10,16,[24][25][26][27]. The sometimes low concordance between the clinical severity of disease (PASI) and quality of life (DLQI) could be due to regional variation in patient numbers and a certain selection bias.…”
Section: Discussionmentioning
confidence: 82%